Some features application of for medical criminal offenses (Journal of actual problems of jurisprudence, 2018)
The main social function of punishment should be considered its preventive function that is included as part of the measures in the fight against crime. At the same time we can not ignore the specifics of reckless criminal who has in most cases, higher value systems than intentional criminal. This feature should determine punishment in sentencing for crimes of negligence is necessary and should take into account the properties collectively characterize the personality of the offender. Therefore humanization trends in the evaluation of properties of the person who commits an act of negligence, is correct. This is to be welcomed in the judicial practice everywhere. In general, extreme measures are already struggle with medical criminal offenses is the application of criminal penalties. The main part of medical criminal offenses related to the categories of small and medium gravity, providing alternative sanctions. Key words: punishment, medical criminal offenses, fines, imprisonment, arrest.